2001
DOI: 10.1007/s11746-001-0374-0
|View full text |Cite
|
Sign up to set email alerts
|

Deodorization of vegetable oils: Prediction of trans polyunsaturated fatty acid content

Abstract: Kinetics of the formation of trans linoleic acid and trans linolenic acid were compared. Pilot plant-scale tests on canola oils were carried out to validate the laboratory-scale kinetic model of geometrical isomerization of polyunsaturated fatty acids described in our earlier publication. The reliability of the model was confirmed by statistical calculations. Formation of the individual trans linoleic and linolenic acids was studied, as well as the effect of the degree of isomerization on the distribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 7 publications
2
37
0
Order By: Relevance
“…octadecadienoic acid (C18:2) was expressed as a ratio between total content of trans isomers and total content of all isomers of C18:1 (c-and t-), resp. C18:2 (Kemény et al 2001). In both oils the DI C18:2 was significantly higher then the DI C18:1 .…”
Section: Resultsmentioning
confidence: 72%
“…octadecadienoic acid (C18:2) was expressed as a ratio between total content of trans isomers and total content of all isomers of C18:1 (c-and t-), resp. C18:2 (Kemény et al 2001). In both oils the DI C18:2 was significantly higher then the DI C18:1 .…”
Section: Resultsmentioning
confidence: 72%
“…In nonhydrogenated oils, trans-18:2 fatty acids are formed by isomerization of linoleic acid during the process of deodorization due to the heat treatment. 23 Consequently, trans-18:2 fatty acids are present in refined soybean, sunflower, corn, peanut, and canola oils, although trans-18:1 levels are very low or undetectable. 24 Furthermore, trans-18:2 fatty acids can be produced during the frying of foods, which raises the possibility that Values are expressed as OR (95% CI).…”
Section: Discussionmentioning
confidence: 99%
“…Kellens (1997) reported that chemical refining should be done at [230][231][232][233][234][235] o C and physical refining at 235-240 o C to obtain deodorized oils with low levels of trans FA (Ͻ 1%). Kemeny et al (2001) found an increase in the relative percentage of isomerized C18:2 and C18:3 acids with an increase in either the deodorization time or the temperature. On the other hand, in this study, the mean values of the degree of isomerization of C18:3 acid were higher than those obtained for the C18:2 acid, while these values for C18:1 acid were found at very low levels for the groups of refined vegetable oils, as expected.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, because of their high consumption, i.e., in the Mediterranean countries, evaluation of the trans FA contents in refined vegetable oils becomes important. In accordance with nutritionists' proposals, there is a strong tendency in the vegetable oil industry to keep the trans FA contents of vegetable oils as low as possible (Kemeny et al, 2001). On the other hand, the US Food and Drug Administration (FDA, 2003) has issued the rule requiring manufacturers to include trans FA or trans fat on the nutrition facts label.…”
Section: Introductionmentioning
confidence: 99%